Soil microbial attributes in rangelands with diferents grazing intensities (Semiárida, 2020)
The soil microbial biomass is the living fraction of organic matter, being responsible for several biological and biochemical processes of the soil and influenced by the conditions imposed by the environment. To evaluate the effect of grazing on changes in soil microbial attributes we studied four grazing intensities based on natural grassland of Pampa Biome: 4, 8, 12 and 16 kg of dry matter per day per 100 kg of animal live weight, compared to an area without grazing. We used randomized block design with two replications. Samples were taken on 11/23/2011 and analyzed to determine the levels of soil organic matter (SOM), microbial biomass, nitrogen, respiration and metabolic quotient. The results showed that at intermediate grazing intensities, such as 12%, minor disturbances occur in soil microbial biomass compared to other intensities, emit less CO2 into the atmosphere for each animal unit produced. The levels of organic matter and soil microbial biomass systems are lower in grazed than in areas excluded from grazing for a long period.
Keywords: Soil organic matter; microbial biomass; microbial respiration; CO2 emission